Immunopathological Roles of Neutrophils in Virus Infection and COVID-19. Issue 3 (September 2021) - Cui, Shu-Nan; Tan, Hong-Yu; Fan, Guo-Chang
Abstract : ABSTRACT: Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has been spread around the world and is currently affecting global public health. Clinical evidence indicates that the elevated number of peripheral neutrophils and higher ratio of neutrophils-to-lymphocytes are correlated with severe outcomes in COVID-19 patients, suggesting the possible immunopathological role of neutrophils during SARS-CoV-2 infection. As an abundant innate immune cell type, neutrophils are well known for their contributions to antimicrobial defense. However, their dysfunction is also associated with different inflammatory signatures during the pathogenesis of infection. Herein, in this mini-review, we summarize the recent progress on the potential role of neutrophils during COVID-19-associated inflammatory responses. In particular, we highlight the interactions between neutrophils and viruses as well as the relationship of neutrophils with cytokine storm and thrombosis in COVID-19 patients. Lastly, we discuss the importance of neutrophils as potential therapeutic targets for COVID-19.